The role of organizational commitment and trust on performance management and the implications for the lecturers’ performance - Anuar Sanusi (Journal of Economics, Business, and Accountancy Ventura, 2015)
The aim of this research is to examine and analyze the effect of the commitment, trust, and performance management on lecturers’ performance. It used a survey on 240 respondents of universities selected randomly. Data were analyzed by using path analysis. It shows that that employees’ trust is affected directly commitment as well as performance management. Performance is affected directly by commitment, and trust as well as employee’s performance management. Based on those findings it can be concluded that any concern toward, commitment, trust, and employees’ per-formance management of Private Higher Education in the Kopertis southern Suma-tera region II have an effect on performance employees. Therefore, commitment, and trust, and employees’ performance management should be put into strategic plan-ning of human resources development in increasing the performance employees of Private Higher Education in the Kopertis southern Sumatera region II, however other variables are necessary to be taken into account properly.